Plastin Family of Actin-Bundling Proteins: Its Functions in Leukocytes, Neurons, Intestines, and Cancer - Hiroto Shinomiya (International Journal of Cell Biology)
Sophisticated regulation of the actin cytoskeleton by a variety of actin-binding proteins is essential for eukaryotic cells to perform their diverse functions. The plastin (also know, as fimbrin) protein family belongs to actin-bundling proteins, and the protein family is evolutionarily conserved and expressed in yeast, plant, and animal cells. Plastins are characterized by EF-hand Ca2+-binding domains and actin-binding domains and can cross-link actin filaments into higher-order assemblies like bundles. Three isoforms have been identified in mammals. T-plastin is expressed in cells from solid tissues, such as neurons in the brain. I-plastin expression is restricted to intestine and kidney; the isoform plays a vital role in the function of absorptive epithelia in these organs. L-plastin is expressed in hematopoietic cell lineages and in many types of cancer cells; the isoform is thus considered to be a useful biomarker for cancer.